Clinical efficacy of diazepam after whiplash: a randomized controlled study - Edin Mešanović; Ćamil Habul; Ermin Hadžić (Medicinski glasnik, 2022)
Aim: To investigate the role of short-term diazepam therapy for improving long-term outcomes and reducing neck pain after whiplash injury. Methods: A total of 89 patients suffering from whiplash injury were included. They were randomly assigned into 2 groups: group A (study group), and group B (control group). The test group was prescribed with diazepam 5 mg tablets one time per day for 7 days and the control group did not get the recommendation to use diazepam. Three previously validated scales, Visual Analogue Pain Scale (VAS), the Neck Disability Index (NDI), and the Whiplash Disability Questionnaire (WDQ), were used at different intervals (7 days, 6 weeks and 6 months after the injury). Results: Among 89 patients, 50 (56.2%) were males, 39 (43.8%) females. The mean age of all participants was 34.80±12.531 years. According to the Mann Whitney U -Test, no significant difference was observed in VAS, NDI, and WDQ scores between the control group and study group at any time point (p>0.05). Conclusion: Diazepam provides no substantial advantage in the treatment of whiplash, and accordingly, we do not recommend diazepam therapy in patients who suffered whiplash injury. The trial was registered in the database of the Federal National Library of Medicine (NLM) (https://clinicaltrials.gov) under clinical trials (unique protocol ID:1703016).
Keywords: neck pain; pain measurement; spasm